An Exploration of Knowledge, Attitudes, and Competencies of Ambulance Nurses in a Pre-Hospital Setting in the Special Region of Yogyakarta - Martani, Hersinta Retno; Purwanta, Purwanta; Kudiyana, Kudiyana; Isnaini, Mifta Yusri; Ari Sadewa, Deskantari Murti; Moh. Yanuar, I Made (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: Trauma-related deaths outside of hospitals predominate over those that occur in hospital settings. Inadequate resuscitation and staff delays in treating patients were two factors that could raise the risk of death in the pre-hospital setting. For sustainable pre-hospital service quality improvement programmes, ambulance nurses’ knowledge, attitudes, and competencies were crucial. This study aims to explore the ambulance nurses’ knowledge, attitudes, and competencies in the Special Region of Yogyakarta (DIY). Methods: This research was a descriptive quantitative study using a cross-sectional design. A total of 54 respondents from Sleman, Bantul, Kulon Progo, Gunungkidul, Yogyakarta, and the DIY Public Safety Center (PSC) were included using total sampling. The research was carried out in September 2023. The Kruskal-Walsis, Man-Whitney, and Spearman rank tests were used to analyse the data. Results: The result of this study showed that the attitude score, which was 69.8 (87.25%), was the greatest score, and the competency score, which was 118.65 (78%), was the lowest. The knowledge, attitudes, and competencies of ambulance nurses variables showed an insignificant result (p-value > 0.05) based on age, gender, educational experience, nurse experience, experience working as an ambulance nurse, or quantity of training completed. Conclusion: According to this study, ambulance nurses' attitudes towards pre-hospital services obtain the greatest marks overall, although their competency in these services still needs more improvement. In conclusion, the knowledge, attitudes, and competencies of ambulance nurses in the Special Region of Yogyakarta did not differ significantly from one another.